Effects of intracyclic velocity variations on the drag exerted by different swimming parachutes - Cortesi, M.; Di Michele, R.; Gatta, G. (The Journal of Strength and Conditioning Research, 2019)
Swimming parachutes are often used as a tool for resisted swimming training. However, little is known on their behavior in terms of exerted drag as a consequence of intracyclic velocity fluctuations. This study aimed to assess the drag provided by 2 swimming parachutes of different shape, also characterized by different volumes and cross-sectional areas, under conditions of velocity variations in the range of those occurring in swimming. A flat square-shaped parachute (FLAT, cross-sectional area and volume: 400 cm2; 0.12 L) and a truncated cone-shaped parachute (CONE, 380 cm2; 7.15 L) were passively towed: (a) at constant velocities ranging from 1.0 to 2.2 m/s, and (b) with velocity fluctuations from 10 to 40% around a mean of 1.6 m/s. At constant velocities, FLAT showed 0.1 N (at 1.0 m/s) to 10.8 N (at 2.2 m/s) higher drag than CONE. For both parachutes, the average drag showed trivial differences between constant and any fluctuating velocity. Conversely, the maximum drag values were higher under conditions of velocity fluctuations than the respective values estimated under stationary instantaneous velocity, although this was observed in CONE only. These findings suggest that swimmers and coaches can select the parachute characteristics based on whether the focus is on increasing/decreasing the average drag or regulating the maximum resistance provided.